Frequency Support Control of a Modular Multilevel Matrix Converter Based Wind Energy Conversion System - Chavez-Orostica, H; Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper discusses the application of the Modular Multilevel Matrix Converter $(M^{3}C)$ to interface Multi-MW Wind Turbines. The modelling and control systems required for this application are analysed and discussed. A Vector Control Strategy based on nested controllers is proposed to provide decoupled operation of the converter, maximum power point tracking capability at the generator-side, and grid code compliance at the grid-side. Additionally, the proposed Strategy uses the energy stored in the floating capacitors of the converter to provide limited frequency support control. Finally, the effectiveness of the proposed control strategy is validated using simulations. © 2018 IEEE.